Elderly people: propensity to be vaccinated for seasonal influenza in Italy. Issue 8 (2nd August 2020) - Marano, Giuseppe; Pariani, Elena; Luconi, Ester; Pellegrinelli, Laura; Galli, Cristina; Magoni, Michele; Piro, Antonio; Scarcella, Carmelo; Biganzoli, Elia M.; Boracchi, Patrizia; Castaldi, Silvana
ABSTRACT: Seasonal influenza continues to be a major cause of illness and death. Vaccination is the most cost-effective prophylaxis to prevent the disease and it is particularly important for people who are at high risk of serious complications derived from influenza, especially for people ≥65 years. In Italy, the influenza vaccination program has been unsuccessful with low rates of uptake in people ≥65 years. We analyzed all the community ≥65 years of the Health Promoting Agency (HPA) of Brescia (northern Italy) to evaluate the propensity attitudes toward influenza vaccination among people ≥65 years in four consecutive seasonal influenza campaigns (from 2014/2015 to 2017/2018). Information about subjects were retrieved from administrative databases. Data from 952, 822 records were analyzed. The prevalence of vaccinated subjects in the four campaigns was 38.6%, 33.7%, 37.7%, and 40.1%, respectively. Among vaccinated people, the frequencies of individuals aged 65–69.9 years were lower than the frequencies of those in the other age classes, with highest frequencies of vaccinated people in the 75–79.9 years age-class. Overall, males showed a slightly higher propensity to be vaccinated and the propensity toward vaccination increased with age in both genders. Suffering from a chronic disease increased the propensity to vaccination; hypertension had the highest impact on the propensity whereas suffering from vasculopathy has the opposite effect. The value of this study is the possibility to know the factors that might indicate a propensity to get an influenza vaccination and to consider a different approach to people ≥65 years with the characteristics indicating a lower propensity to vaccination.